Increasing and justification of demand for the modernization of agricultural machinery - Bulgakov, Volodymyr; Movchan, Vitalii; Мовчан, Віталій Федорович; Мовчан, Виталий Федорович; Ihnatiev, Yevhen; Ігнатьєв, Євген Ігорович; Игнатьев, Евгений Игоревич; Mitkov, Vasyl; Мітков, Василь Борисович; Митков, Василий Борисович (My University, 2020)
The paper presents a technical and economic background to the need for modernization of modern tractors and combines. The presented method allows forecasting the demand for modernization of equipment. It allows to develop the program of action to improve the quality of machines, assess their real potential, develop of strategic and operational planning for the development of modernization, organize activities of the technical service. This article proposes a method for determining the demand for modernization of agricultural machinery in technical, repair and technical enterprises, based on the analysis of statistical and expert data characterizing their influence on the demand for research. It is justified that repair company must confidently organize an active advertising campaign to promote modernized machines to the market.
Keywords: means of mechanization; analytical method; costs; optimum; technology; yield